Ichnology and sedimentology reveal depositional characteristics of bay-margin parasequences in the Miocene Amazonian foreland basin - Gingras, Murray K. (2002)
Proposed depositional models for Miocene Amazon foreland basin strata (Pebas Formation, Peru) are controversial. Recent depositional models include lacustrine and tidally influenced, brackish-water embayment. This paper presents data that support tidally influenced, brackish-water deposition for at least part of Pebas time (10-14 Ma). Two parasequences are presented (Santa Julia and Tamshiyacu). Both crop out along the Amazon River in Upper Amazonia near Iquitos, Peru. At these locations, abundant evidence of brackish-water, tidally influenced deposition is documented, including marginal marine bioturbation, sedimentary couplets, semidiurnal couplets (preserved in burrows), and pinstripe lamination. The deposits are locally highly bioturbated. At both locations ichnogenera normally associated with marine to brackish-water depositional environments are common. Three normally marginal-marine ichnofabrics are reported: (1) a Chondrites-reburrowed, Planolites ichnofabric resident only in massive-appearing muds; (2) a Scolicia (Laminites), Thalassinoides, Ophiomorpha ichnofabric that is manifested as intensely bioturbated silty sands; and (3) a Thalassinoides-generated ichnofabric that is interpreted to have descended into consolidated substrates and is thus representative of the Glossifungites Ichnofacies. Several trace fossils contain laminated infills organized into distinct sedimentary couplets that are best interpreted as resulting from semidiurnal processes. Six conclusions are arrived at: (1) sedimentological and ichnological data consistently indicate that sediment accumulation dominantly occurred in sporadically dysaerobic, marine to brackish water, under a tidal influence; (2) sediment accumulation occurred in bay-margin environments that prograded into a shallow, quiescent bay; (3) a stratified water column is indicated by the ichnofauna; (4) low accommodation space, repetitive and rapid adjustments of relative sea level, shallow wave base, and a stratified water column combined to generate an atypical parasequence architecture; (5) previously published isotopic data are consistent with sediment accumulation in brackish to marine water; and (6) marine incursion into Amazonia occurred during the Middle Miocene.